In Vitro Activity of Rifampin Alone and in Combination with Nafcillin and Vancomycin Against Pathogenic Strains of Staphylococcus aureus - Tuazon, Carmelita U. (1978)
Twenty strains of Staphylococcus aureus isolated from patients with endocarditis were examined in vitro for susceptibility to rifampin, nafcillin, and vancomycin and to combinations of rifampin with nafcillin or vancomycin. Minimum bactericidal concentrations of rifampin ranged from 0.0031 to 0.0125 μg/ml, of nafcillin ranged from 0.078 to 0.312 μg/ml, and of vancomycin ranged from 0.312 to 1.25 μg/ml. The combination of rifampin with nafcillin was synergistic for 12 strains; the combination of rifampin plus vancomycin was synergistic for 5 of the isolates.